DAMPAK PERNIKAHAN DINI TERHADAP PENDIDIKAN ANAK DALAM KELUARGA DI DUSUN LAOK SONGAI KEC. KOKOP BANGKALAN - Umriyeh; Dian Eka Indriani; Anindita Trinura Novitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the impact of early marriage on children's education in families in Laok Songai Hamlet, District. Kokop, Bangkalan.Early marriage is a phenomenon that still occurs frequently in this area, with various factors influencing it, such as culture, economics and the level of education of parents. This research uses a qualitative method with a descriptive approach, where data is collected through observation, interviews and documentation. The research results show that early marriage has a negative impact on children's education, both directly and indirectly. Children from families with early marriages tend to have higher school dropout rates, lower academic achievement, and a lack of motivation to continue their education to a higher level. Apart from that, early marriage also affects the quality of education in the family, where parents who marry early are less able to provide adequate guidance and support to their children. These findings indicate the need for intervention from various parties, including the government, educational institutions and society, to reduce the prevalence of early marriage and increase awareness of the importance of education for children's future.